Thinking in Islands; The Portuguese perception of the Indonesian archipelago and particularly of Sunda in early texts and charts - Langguth, Svann (Wacana, Journal of the Humanities of Indonesia, 2012)
This article discusses various early sources on the Indonesian archipelago. It starts with the status of knowledge before the first voyage of the Portuguese to the Moluccas from accounts of travellers to insular Southeast Asia in the Middle Ages and the picture on world maps European cartographers produced. Comparing that view with text sources and the resulting geographic material of the first expeditions by the Portuguese provides an insight into contemporary mechanisms of knowledge transfer. Certain effects can be traced and are repeated on different levels of access to the original facts mainly because most maps were drawn up in Europe but based on the geographic description provided by text accounts. An abundance and multiplication of failures and mistakes is evident and is partly related to the scarcity of sources and due to reproduction techniques.